A new species Rubia urceolata (Rubiaceae: Rubieae) from Shennongjia National Park, central China - Wang, Chun-Hui; Liu, Zhi-E; Li, Ya; Wang, Xiao-Fan (Phytotaxa, 2018)
Rubia urceolata, a new species endemic to Shennongjia National Park, Hubei Province (central China), is herein described and illustrated. The new species has sub-orbicular to ovate leaves and mericarp berry, which might be confused with the closely related species R. ovatifolia. However, R. urceolata can be distinguished from R. ovatifolia by its urceolate corolla, longer corolla tube (1.3–2 mm) and flowers with purplish red lobes. Morphological comparisons with R. ovatifolia are discussed.